PLASTY RECURRENT POSTOPERATIVE ABDOMINAL WALL HERNIA. CLINICAL AND ANATOMICAL OBSERVATION OF THE PATIENT AFTER 13 YEARS OF THE PLASTY - M. B. Skvortsov (Неотложная медицинская помощь, 2016)
ABSTRACT. Postoperative abdominal wall hernias account for 20-26% of all external abdominal hernias and occur in 10 - 32% of the patients operated on the abdominal organs. They are characterized by a rapid increase in size, high rate of complications. There is no standard operation. Relapses occur in 14–15%. Autoplastic ways by fascial-aponeurotic plasty are not always reliable and radical. Alloplastic methods have been widely spread and used in 75–85% of operated in Europe and in the USA. These methods are not flawless- changes of the implants properties and their capsule were marked — their size, flexibility and strength are decreased, complications — adhesions, fistulas, pain and discomfort. Therefore, the search for radical ways remains relevant. The description of the clinical follow-up after successful local fascial-aponeurotic plastic surgery of the repeatedly recurrent postoperative abdominal wall hernia. Conclusion The author recommends the wider use of the described method of hernioplasty.